# Algebra II (check)

posted by .

Assume that no denominator equals 0.

sqrt12 - sqrt18 + 3sqrt50 + sqrt75

= (sqrt2^2*3) - (sqrt2*3^2) + (3sqrt2*5^2) + (sqrt3*5^2)

= (sqrt2^2*sqrt3) - (sqrt3^2*sqrt2) + (3sqrt5^2*sqrt2) + (sqrt5^2*sqrt3)

= (2*sqrt3) - (3*sqrt2) + (3sqrt5*sqrt2) + (5*sqrt3)

= 7sqrt3 + sqrt2 + sqrt5(answer)

• Algebra II (check) -

no, your roots 3's are ok, but....

sqrt12 - sqrt18 + 3sqrt50 + sqrt75
= √(4*3) - √(9*2) +3√(25*2) + √(25*3)
= 2√3 - 3√2 + 15√2 + 5√3
= 7√3 + 12√2

## Similar Questions

1. ### more math

sqrt50/sqrt2 (sqrt50)/(sqrt2)*(sqrt2/sqrt2)= (sqrt50*sqrt2)/2 =sqrt100/2=10/2=5 Check my thinking. thanks... what does this equal: 3sqrt2+4sqrt2 3 times the square root of 2 PLUS 4 times the square root of 2. This would equal 7 times …
2. ### algebra

Can someone please check my work on this problem?
3. ### ALGEBRA 1

change 50 to 25*2 sqrt 50 = 5 sqrt2 change 8 to 4*2 Nope: (sqrt3-sqrt5)(sqrt3-sqrt5). remember (a-b)(a-b)= a^2-2ab + b^2 Simplify.Express in simpliest radical form. 1.3sqrt2 +sqrt50 Cannot be solve. Terms have unlike radicals 2.3sqrt8+2 …
4. ### Algebra

Find the exact solution(s) of the system: x^2/4-y^2=1 and x=y^2+1 A)(4,sqrt3),(4,-sqrt3),(-4,sqrt3),(-4,-sqrt3) B)(4,sqrt3),(-4,sqrt3) C)(2,1),(2,-1),(4,sqrt3),(4,-sqrt3) D)(4,sqrt3),(4,-sqrt3) I don't know
5. ### Math

Find the exact solution(s) of the system: x^2/4-y^2=1 and x=y^2+1 A)(4,sqrt3),(4,-sqrt3),(-4,sqrt3),(-4,-sqrt3) B)(4,sqrt3),(-4,sqrt3) C)(2,1),(2,-1),(4,sqrt3),(4,-sqrt3) D)(4,sqrt3),(4,-sqrt3)
6. ### Algebra

Rationalize denominator, all variables positive real numbers and denominator is not zero. sqrt3/3 sqrt2 - sqrt3 sqrt3(3sqrt2+sqrt3)/18-3 3 sqrt6+3/18-3 3 sqrt 6+3/15 (is this my answer)
7. ### trigonometry

Find the equation of a line passing through the origin so that the tangent of the angle between the line in quadrantI and the positive x-axis is sqrt3/3. A. y=sqrt3/3x B. y=sqrt3x C.y=x D.y=sqrt2/2x thnks alot:)
8. ### Algebra 2

1. Simplify: sqrt6(sqrt2/2+sqrt3)-sqrt8 2. Simplify: sqrt(72x^3)-5x sqrt(2x) 3. Simplify: (2sqrt6-sqrt3)^2 4. Simplify: 6/3+2sqrt3 5. Solve: 2-y=sqrt(y+4) I need all of the steps. Thanks
9. ### trig

Write the expression and evaluate. There is only one answer whIch should match the range of the inverse trig function. Sec^-1(-2) Sec^-1(-sqrt2) Tan^-1(-sqrt3) Tan^-1(sqrt3)
10. ### Precalculus

Given: f(x) = X^2-x evaluate: f(sqrt2 + 3) I have worked out this and am stuck: (sqrt2+3)^2 - (sqrt2+3) (sqrt2+3)*(sqrt2+3)- (sqrt2 +3) (sqrt2)^2+ 3sqrt2 +3sqrt2+ 9- (sqrt2+3) 2+6sqrt2 +9-sqrt2-3 and am stuck or wrong here. Ans= SQRT2+6sqrt2 …

More Similar Questions